Flexibility is the key to tuning the transport properties of fluorinated imide-based ionic liquids. Issue 32 (3rd August 2022) - Philippi, Frederik; Rauber, Daniel; Palumbo, Oriele; Goloviznina, Kateryna; McDaniel, Jesse; Pugh, David; Suarez, Sophia; Fraenza, Carla C.; Padua, Agilio; Kay, Christopher W. M.; Welton, Tom
Abstract : The interplay of fluorination, flexibility, and mass affects the transport properties of imide ionic liquids. Here we show how the combination of experimental and theoretical techniques can disentangle such confounding variables. Abstract : Ionic liquids are becoming increasingly popular for practical applications such as biomass processing and lithium-ion batteries. However, identifying ionic liquids with optimal properties for specific applications by trial and error is extremely inefficient since there are a vast number of potential candidate ions. Here we combine experimental and computational techniques to determine how the interplay of fluorination, flexibility and mass affects the transport properties of ionic liquids with the popular imide anion. We observe that fluorination and flexibility have a large impact on properties such as viscosity, whereas the influence of mass is negligible. Using targeted modifications, we show that conformational flexibility provides a significant contribution to the success of fluorination as a design element. Contrary to conventional wisdom, fluorination by itself is thus not a guarantor for beneficial properties such as low viscosity.